2021
DOI: 10.17219/acem/130356
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 6: biological significance and role in inflammatory bowel diseases

Abstract: Cytokines affect a number of processes in the living body. Interleukin 6 (IL-6) is a cytokine involved in inflammation, infection response and also regulation of metabolism. It stimulates target cells through a membranebound IL-6 receptor. Inflammatory bowel diseases (IBD) are autoimmune diseases whose incidence and prevalence are increasing worldwide. It is a group of chronic gastrointestinal disorders characterized by multifactorial, still unknown pathogenesis, varied symptomatology, course with periods of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Most importantly, we have shown that increased systemic IL-6 had strong association with altered human gut resistome in GW Veterans. IL-6 has been shown to be a pleiotropic cytokine and is key to gastrointestinal disturbances, and cognitive deficits 42 , 43 . Recent advances in understanding the host resistome improved our knowledge about evolution, origins and emergence of antibiotic resistance though the field is continuously evolving 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, we have shown that increased systemic IL-6 had strong association with altered human gut resistome in GW Veterans. IL-6 has been shown to be a pleiotropic cytokine and is key to gastrointestinal disturbances, and cognitive deficits 42 , 43 . Recent advances in understanding the host resistome improved our knowledge about evolution, origins and emergence of antibiotic resistance though the field is continuously evolving 44 .…”
Section: Discussionmentioning
confidence: 99%
“…The main factor responsible for the altered iron metabolism in IBD is hepcidin, whose secretion is induced by inflammatory cytokines (IL-1β and IL-6). 3 , 16–18 , 38 Hepcidin acts by binding to the only known iron exporter protein FPN-1, causing its internalization and degradation. 14 , 39 Accordingly, we observed a decrease of FPN-1 in both patients with CD and UC, as compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 Altered cytokine production has a pivotal role in the pathogenesis of IBD, causing an inflammatory state both at local and systemic levels. 3 , 4 In 10% to 40% of cases, patients with IBD present extraintestinal manifestations, 5 , 6 among which the most frequent are those affecting the bone tissue, such as osteoporosis (OP). 7 , 8 Bone mass is mostly acquired during childhood, and the early onset of IBD may compromise the final bone mineral density, affecting growth.…”
Section: Introductionmentioning
confidence: 99%
“…We also linked the association of systemic inflammation and an altered gut resistome that is linked to increased circulating proinflammatory cytokine IL6, intestinal pathology and neurotrophic factor BDNF. IL6 has been shown to be a pleiotropic cytokine and is key to gastrointestinal disturbances, and cognitive deficits [53], [54]. Recent advances in understanding the host resistome improved our knowledge about evolution, origins and emergence of antibiotic resistance though the field is still evolving [55].…”
Section: Discussionmentioning
confidence: 99%